Wakalah bi al-Istitsmar dalam Mekanisme Penghimpunan Dana di Lembaga Keuangan Syariah (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This study is intended to examine the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) regarding Fundraising under the Wakalah bi al-Istismar Agreement which provides greater opportunities for Islamic financial institutions in Indonesia in raising and managing capital. This study uses a document approach by using the DSN-MUI fatwa Number 152 of 2022 as the main source, and analyzed using a qualitative approach. This study shows that the DSN-MUI fatwa has provided additional options for savings and deposit products in Islamic financial institutions, namely wakalah bi al-istismar. Thus, the level of customer needs which is a priority through the addition of various alternative contracts, is expected to be able to attract many customers, especially in the fundraising mechanism in Islamic banking. It's just that the use of the contract does not apply to all fundraising products, but only to certain products that have been determined.